iPad applications that required a range of motor skills promoted motor coordination in children commencing primary school - Axford, C.; Joosten, Annette; Harris, C. (Wiley-Blackwell Publishing Asia, 2018)
© 2018 Occupational Therapy Australia Background/aim: Children are reported to spend less time engaged in outdoor activity and object-related play than in the past. The increased use and mobility of technology, and the ease of use of tablet devices are some of the factors that have contributed to these changes. Concern has been raised that the use of such screen and surface devices in very young children is reducing their fine motor skill development. We examined the effectiveness of iPad applications that required specific motor skills designed to improve fine motor skills. Method: We conducted a two-group non-randomised controlled trial with two pre-primary classrooms (53 children; 5–6 years) in an Australian co-educational school, using a pre- and post-test design. The effectiveness of 30 minutes daily use of specific iPad applications for 9 weeks was compared with a control class. Children completed the Beery Developmental Test of Visual Motor Integration (VMI) and observation checklist, the Shore Handwriting Screen, and self-care items from the Hawaii Early Learning Profile. Results: On post testing, the experimental group made a statistically and clinically significant improvement on the VMI motor coordination standard scores with a moderate clinical effect size (P  <  0.001; d = 0.67). Children's occupational performance in daily tasks also improved. Conclusion: Preliminary evidence was gained for using the iPad, with these motor skill-specific applications as an intervention in occupational therapy practice and as part of at home or school play.